A Single Center Study Using CT Enterography to Evaluate Small Bowel Disorders - Kalsoom Nawab, Anwar Ul Haq, Mehmood Akhtar Khattak, Hina Gul, Naheed Khan, Irsa Shoaib, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A research was done on the efficiency of identifying small intestinal problems using computed tomography (CT) enterography. The findings showed that 93% of patients had appropriate diagnoses, while the remaining [07%] were still pending. These results indicate that CT enterography is a highly accurate, safe, and cost-effective imaging method for the diagnosis of small intestinal diseases. Aim: By using CT enterography as an imaging method, small intestinal problems may be precisely identified. Its cost-efficiency in comparison to other imaging modalities, as well as its safety and effectiveness in identifying small bowel illnesses, have been assessed. Additionally, various imaging modalities have been compared to CT enterography's accuracy, and its effect on patient outcomes has also been taken into account. Method: The Radiology Department of KTH Peshawar conducted a comprehensive research with hundred patients between Jan 2017 and jan 2018. Each patient performed a CT enterography, and based on precise data gathered from their medical records, their clinical findings were compared with the results, which were then assessed using SPSS Version 27. A descriptive statistical analysis was then performed on the data. Results: In our investigation, CT enterography had a good 93% diagnostic success rate in the diagnosis of small intestinal diseases. Unfortunately, for certain individuals, notably the remaining 7%, the findings were not conclusive. We found it interesting that CT enterography had a greater accuracy rate than other imaging methods like MRI and ultrasound. Conclusion: This research established CT enterography as a cost-efficient, secure, and accurate imaging method for the diagnosis of small intestinal illnesses. This non-invasive method also has high accuracy and safety. Keywords: imaging modalities, accuracy, cost-effectiveness, safety, and CT enterography.